A comparative assesment of some parametric and non- parametric option pricing models: an application with S & P 500 index options - Gençer, Murat (My University, 2001)
Bu çalışmada literatürde ki farklı opsiyon fiyatlandırma modelleri incelenmiş ve gerçekleşmiş olan piyasa fiyatını en iyi tahmin etme açısından birbirleriyle mukayese edilmiştir. Sırasıyla, Black-Scholes, GARCH, Stochastic Volatility, Semi-Parametric ve Fully-Non-Parametric opsiyon fiyatlandırma modelleri, S&P 500 indeksinin 1993 yılında gerçekleşen 14,431 tane alım opsiyon fiyatı üzerinde uygulanmıştır. Sonuçta, opsiyon fiyatlamasında ki en önemli değişkenin fiyat oynaklığı olduğu bulunmuş ve bu değişkenin Non-Parametric tekniklerle modellendikten sonra Black-Scholes formülünde veri olarak kullanıldığı, Semi-Parametric opsiyon fiyatlama modelinin diğer modellere göre daha başarılı sonuçlar verdiği gözlemlenmiştir.

ABSTARCT This study examines different option pricing models and compares the relative performance of them, in terms of estimating the value of the option correctly. Five models namely: Black-Scholes, GARCH, Stochastic Volatility, Semi-Parametric and Fully-Non-Parametric regression techniques are applied to the S&P500 index options (14,431 call options) traded between Jan 2, 1992 and Dec 31,1993. It is found that, the key determinant of option prices is the volatility of the underlying asset, and the method which can model the volatility dynamics better, could price the value of the options more precisely. In addition to this, the study indicates that the theoretical framework of the Black-Scholes formula is strong enough and if the volatility is calculated correctly, Black-Scholes can perform better. Finally, according to Mean Absolute Percentage Errors and Root Mean Square Errors, it is concluded that the Semi-Parametric Option Pricing Model -where the volatility is found by the non-parametric regression technique and then used in the Black-Scholes formula as a volatility parameter- results in less pricing errors when compared to other models.
Keywords: FİYAT BELİRLEME